PENGARUH PERTUMBUHAN EKONOMI, UPAH MINIMUM, PENDIDIKAN DAN GENDER TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN/KOTA PROVINSI JAWA TIMUR - ELGA BRILLIAN VIDIASARI (Jurnal Ilmiah Mahasiswa FEB, 2015)
This study examines the effects of changes in economic growth, minimum wage, education and gender  of employment in 38 residence/city in the Province of East Java data set from 2008 to 2014. This study is backgrounded by the unbalanced of demand and supply in employment market. Province of East Java has the biggest numbers of employment than the other provinces of Java.  If they aren’t used effectively, they will be unemployment that can be nation problem. In this research used panel data combination of 38 residence /city in the Province of East Java as cross section data and series of year 2008-2014 as time series data. The result of this research determined that economic growth, education, gender affect positively to the employment in 38 residence/city in the Province of East Java, meanwhile minimum wage affect negatively to the employment in 38 residence/city in the Province of East Java.Keyword: economic growth, minimum wage, education, gender and employment